Eclipse Computation Tables in Sanskrit Astronomy: A Critical Edition of the Tables of the Karaṇakesarī of Bhāskara (fl. c. 1681) - Misra, Anuj; Montelle, Clemency; Plofker, Kim (History of Science in South Asia)

(untitled) (University of Alberta Library, 2016)
We present here a critical edition of the numerical tables of the Karaṇakesarī, an eclipse-computation table-text authored by Bhāskara in the latter half of the 17th century, and known to us from three manuscripts.